Multimedia Interaktif Sebagai Media Pembelajaran Pada Masa Pandemi Covid 19 - Manurung, Purbatua (STAI Serdang Lubuk Pakam, 2020)
This study aims to analyze the function of alternative learning media (interactive multimedia) during the Covid 19 pandemic. This research uses qualitative research methods based on library research (library research). Collecting data using documentation techniques derived from library sources. Data analysis uses content analysis techniques where each source or literature used is adjusted and the context's suitability is seen with other literature from books, journals or other research. Applications and multimedia content can be used as a learning resource during online learning, and ensure that the learning process remains active even though it is not done face-to-face. This involves all facilities and support to ensure online learning can be done starting from internet access, devices in the form of smartphones or notebooks, and the availability of adequate signals. Multimedia also makes it possible to increase children's interest and motivation to learn, which often decreased during the Covid 19 period. Multimedia is also a step to stimulate student understanding of the material being taught accelerated.